Perencanaan Keuangan Pribadi dalam Persiapan Menghadapi Ancaman Resesi Ekonomi 2023 - Tio Prasetio; Reni Hariyani (LPPM Universitas BSI, 2023)
Prediction the world economy will facing brink economic recessionÂ 2023 is phenomenon marked by symptoms simultaneous increase in benchmark interest rates carried out from several central banks in the world. Threat recession encourages every individual, including students, to be able carry out personal financial planning properly and wisely. Research purpose was to describe students perceptions personal financial planning in preparation for the threat economic recession 2023. The research method used was descriptive qualitative with sample 200 respondents. With data analysis using score interpretation. Results this research indicate that students already know the importance emergency funds preparation for the threat economic recession. However, students personal financial planning is still low, reflecting low preparation for the threat economic recession 2023. InterpretationÂ this research the low level of student awareness in cultivating habit of saving, not being able to make savings and not preparing budget and recording income and expenses. The novelty in research use topic regarding personal financial planning by students at the conditions COVID-19 pandemic and preparations economic recession. And the other noveltyÂ indicators used describing personal financial planning.